Spatial patterns of mixing in the Solomon Sea. Issue 5 (15th May 2017) - Alberty, M. S.; Sprintall, J.; MacKinnon, J.; Ganachaud, A.; Cravatte, S.; Eldin, G.; Germineaud, C.; Melet, A.
Abstract: The Solomon Sea is a marginal sea in the southwest Pacific that connects subtropical and equatorial circulation, constricting transport of South Pacific Subtropical Mode Water and Antarctic Intermediate Water through its deep, narrow channels. Marginal sea topography inhibits internal waves from propagating out and into the open ocean, making these regions hot spots for energy dissipation and mixing. Data from two hydrographic cruises and from Argo profiles are employed to indirectly infer mixing from observations for the first time in the Solomon Sea. Thorpe and finescale methods indirectly estimate the rate of dissipation of kinetic energy ( ϵ ) and indicate that it is maximum in the surface and thermocline layers and decreases by 2–3 orders of magnitude by 2000 m depth. Estimates of diapycnal diffusivity from the observations and a simple diffusive model agree in magnitude but have different depth structures, likely reflecting the combined influence of both diapycnal mixing and isopycnal stirring. Spatial variability of ϵ is large, spanning at least 2 orders of magnitude within isopycnal layers. Seasonal variability of ϵ reflects regional monsoonal changes in large‐scale oceanic and atmospheric conditions with ϵ increased in July and decreased in March. Finally, tide power input and topographic roughness are well correlated with mean spatial patterns of mixing within intermediate and deep isopycnals but are not clearly correlated with thermocline mixing patterns. Plain Language Summary: In the ocean, a number of physical processes move heat, salt, and nutrients around vertically by mixing neighboring layers of the ocean together. This study investigates the strength and spatial patterns of this mixing in the Solomon Sea, which is located in the tropical west Pacific Ocean. Estimates of the strength of mixing are made using measurements of temperature, salinity, and velocity taken during two scientific cruises in the Solomon Sea. Measurements of temperature and salinity from a network of floats that move up and down through the ocean and travel with ocean currents were also used to estimate the strength and patterns of mixing. This research finds three key results for mixing in the Solomon Sea: (1) Mixing is strongest near the surface of the Solomon Sea and less strong at deeper depths. (2) Mixing varies horizontally, with stronger mixing above underwater ridges and seamounts, and with weaker mixing above smooth and flat seafloor. (3) The strength of mixing changes with the seasons, possibly related to the monsoonal winds which also change in strength over the seasons. Key Points: Within isopycnal layers dissipation varies by at least 2 orders of magnitude in the Solomon Sea Dissipation is maximum in the surface and decreases by 2–3 orders of magnitude by 2000 m depth Dissipation is seasonally variable, particularly in the thermocline